Structural adjustment in sub-Saharan Africa - Lensink, Robert (London ; New York : Longman, 1996)
The book presents a non- partisan assessment of the economic arguments for and against Structural Adjustment Programme(SAP) in Africa and provides two views of the programmes: world and the IMF and that of their critics.
Includes bibliographical references (p. 134-140) and indexes.
opc 29/09/16
Loans
Keywords: Structural adjustment (Economic policy); Adjustment programmes